The combined impact of student sports, physical education, and outdoor activities, based on the digital Triple Helix model, creates a synergistic effect - Grigoriev V.I. ,; Panchenko I.A. ,; Vasiliev D.A. ,; Novitsky Ya.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. This research is aimed at expanding the possibilities of the "triple helix" integration model, combining student sports, physical education and active recreation, through the use of digital tools. Methods and structure of the study.Aspart of the research,using the methods of the FactoMineR package, a digitaltriplehelixplatformwasdevelopedformanagingphysicaleducationin the studentenvironment.Theprojectinvolvedstudents of bothsexesaged18-19years,representing286academicgroups.Theeffectiveness of the proposedmodel was evaluatedon the basis of a number of confirmedindicatorsrecordedinsuchdisciplinesas 100-meter running, 100-meterswimming, pull-ups, push-ups,aswell as whenpassing the TRP standards. Results and conclusions. The results of the work confirmed the scientific validity of the approach to integrating the key elements of the discipline "Physical Culture and Sport" – student sports, physical education and active leisure – based on the Triple Helix platform. The introduction of digital technologies into various aspects of physical education contributes to the expansion of the management capabilities of the Triple Helix in the context of the interaction of student sports, physical education and active leisure. It has been confirmed that digital regulation makes it possible to achieve a synergetic effect in the development of the scientific and technical potential of students' physical education. The effectiveness of the use of digital technologies to optimize the use of state and public resources in order to promote health, develop physical activity and improve athletic skills of students has been proven.